Oculohypotensive Effect of Nitric Oxide Donor in Glaucomatous Male Rabbits - Mustafa Ghazi Al-Abbassi (Journal of Global Pharma Technology, 2018)
Objective: The aim of present study was to evaluate the effect of topical nitric oxide donor in lowering intraocular pressure of glaucomatous male rabbits. Method: Thirty two albino rabbits weighing (2.5-3.5 kg) were used in the study and allocated into four groups include: normal group, glaucoma induced group, sodium nitroprusside (SNP) group and timolol group. Glaucoma induction was done by single intravitreal injection of 50 units of freshly prepared alpha-chymotrypsin in 0.1 ml of sterile saline. The treatment was applied twice daily: at 9:00 a.m. and at 1:00 p.m. during 12 day. The intraocular pressure was recorded two times a day: at 9:00 a.m. and at 12:00 p.m. The parameters that measured include; the intraocular pressure, pupil diameter, corneal sensation, light reflex, conjunctival redness and cyclic guanosine monophosphate (cGMP) level in aqueous humor. Results: The results revealed a high significant decrease in intraocular pressure and a high significant increase in cyclic guanosine monophosphate level, also no variation in pupil diameter, positive pupillary response to light, no corneal sensation, and no conjunctival redness were observed. Conclusion: The findings suggest that sodium nitroprusside has oculohypotensive action and it may prove to be an additional effective for the management of glaucoma.Keywords: Glaucoma, Nitric oxide donor, intraocular pressure.